Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Pegawai Di Puskesmas Sabbangparu Kabupaten Wajo - Agni Ayulia Ayustira; Fatmah Afrianty Gobel; Sumiaty; Ikhram Hardi S; Farihah Muhsanah (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Work fatigue is an occupational health problem that can increase the risk of accidents and reduce productivity. Data shows that work accidents remain high, and some are caused by work fatigue. This study aims to determine the factors associated with work fatigue among employees at the Sabbangparu Community Health Center in Wajo Regency in 2024. This study used a quantitative, cross-sectional design. The study population comprised all 68 employees at the Sabbangparu Community Health Center, with a total sampling approach, yielding 68 respondents. Data analysis was performed using the chi-square test to determine the relationship between variables. The results showed that work shifts (p = 0.009), length of service (p = 0.030), and workload (p = 0.011) were related to work fatigue. Meanwhile, there was no relationship between work period (p = 0.443) and nutritional status (p = 0.387) with work fatigue. This study concludes that work shifts, length of service, and workload are associated with work fatigue, whereas work period and nutritional status are not. Therefore, it is recommended that the Community Health Center pay closer attention to workload scheduling and employee rest times to prevent excessive work fatigue.